Dancing language - dancing society: Characteristics of Thai dance art terminology - Rattanawijan, Surangkhanang; Srimuang, Daraporn (RMUTSB ACADEMIC JOURNAL (HUMANITIES AND SOCIAL SCIENCES), 2025)
This article aimed to project the characteristics of language in Thai dance art by studying dancing art terminology or choreographic naming, and the current language use in the conversations of Thai dance art and in various other contexts within the field. The study showed that the language in Thai dance art was a terminology inherited as teaching practice of Thai dance art. Thus, it is implied that the terminology has been influenced by teaching values, rooted in ‘tradition’ or customs, driven by the belief in respecting the ‘teacher’. As a result, the unique characteristics of society and teaching practice have considerably maintained the language used in Thai dancing art as a unique terminology.